2003
DOI: 10.2190/01wu-9dmf-2xvn-7wyu
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Students for a Distance Learning Environment: A Comparison of Learning Strategies of in-Class and Distance Learners

Abstract: By 2010, college enrollments are expected to increase by one-third, yet this growth happens at a time when colleges and universities are faced with limited or reduced funding [1]. The result is a demand for cost-effective methods of instruction like distance learning [2]. But to be successful in a distance learning environment, students must not only be self-disciplined but also have effective learning skills [3]. What learning skills do the students need and how can they acquire them? This article examines th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…DL is not new to education; correspondence schools have operated in the US institutions such as Pennsylvania State University which is one of the first universities that had a program of correspondence study in 1892 (Banas and Emor, 1998). Today distance education exists worldwide and is applied to education at different levels (Sizoo et al, 2003).…”
Section: Literature Review Distance Learningmentioning
confidence: 99%
“…DL is not new to education; correspondence schools have operated in the US institutions such as Pennsylvania State University which is one of the first universities that had a program of correspondence study in 1892 (Banas and Emor, 1998). Today distance education exists worldwide and is applied to education at different levels (Sizoo et al, 2003).…”
Section: Literature Review Distance Learningmentioning
confidence: 99%
“…Students must be self-disciplined (Li, 2002) and possess effective learning skills and coping mechanisms to be successful in distance learning environments. Sizoo, Malhotra, and Bearson (2003) found that controlling anxiety, for instance, contribute to a successful learning experience; the authors suggest that students can reduce anxiety by regaining control over their academic responsibilities and overstudying recommended materials.…”
Section: Distance Learners Who Successfully Complete Coursesmentioning
confidence: 99%
“…OL is not new to education; correspondence schools have operated in the United States such as Pennsylvania State University which is one of the first universities that has a program of correspondence study in 1892 (Banas and Emor, 1998). Today online education exists worldwide and is applied to education at different levels (Sizoo et al, 2003).…”
Section: Online Learningmentioning
confidence: 99%